2022
DOI: 10.1111/jfb.15114
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding and species delimitation of the genus Oxynoemacheilus (Teleostei: Nemacheilidae) in Anatolia

Abstract: The DNA barcoding approach was used for the determination of evolutionary relationships and species delimitation of the genus Oxynoemacheilus (Teleostei: Nemacheilidae). The COI barcode region (615 bp amplicon) was used to barcode 444 individuals from 64 morphologically identified species in the genus Oxynoemacheilus and 189 haplotypes were identified. The average of the interspecific p distance (9.59%) was about 21-fold higher than the average intraspecific distance (0.44%). A general genetic threshold of 1.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
3
5
0
Order By: Relevance
“…This study reflected that the phylogenetic relationships of Oxynoemacheilus based on the COI barcoding gene region are in agreement with the previous research (Bektaş et al, 2022; Geiger et al, 2014; Sayyadzadeh et al, 2016; Turan et al, 2019). Similar to the previous study by Bektaş et al (2022) Oxynoemacheilus genus was determined to be polyphyletic. Bektaş et al (2022) determined the COI‐based threshold value of 1.46% based on the genetic distance range.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study reflected that the phylogenetic relationships of Oxynoemacheilus based on the COI barcoding gene region are in agreement with the previous research (Bektaş et al, 2022; Geiger et al, 2014; Sayyadzadeh et al, 2016; Turan et al, 2019). Similar to the previous study by Bektaş et al (2022) Oxynoemacheilus genus was determined to be polyphyletic. Bektaş et al (2022) determined the COI‐based threshold value of 1.46% based on the genetic distance range.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the previous study by Bektaş et al (2022) Oxynoemacheilus genus was determined to be polyphyletic. Bektaş et al (2022) determined the COI‐based threshold value of 1.46% based on the genetic distance range. Also, Sayyadzadeh et al (2016) suggested an appropriate species‐level threshold for the Oxynoemacheilus COI genetic divergences of 1.4%.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations